2018
DOI: 10.7150/thno.25784
|View full text |Cite
|
Sign up to set email alerts
|

HSP40 co-chaperone protein Tid1 suppresses metastasis of head and neck cancer by inhibiting Galectin-7-TCF3-MMP9 axis signaling

Abstract: Human tumorous imaginal disc (Tid1), a DnaJ co-chaperone protein, is classified as a tumor suppressor. Previously, we demonstrated that Tid1 reduces head and neck squamous cell carcinoma (HNSCC) malignancy. However, the molecular details of Tid1-mediated anti-metastasis remain elusive.Methods: We used affinity chromatography and systemic mass spectrometry to identify Tid1-interacting client proteins. Immunohistochemical staining of Tid1 in HNSCC patient tissues was examined to evaluate the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Herein, by using PDX models, we tested the feasibility of the cell membrane‐coated nanoplatform in a preclinical cancer treatment scenario. Head and neck squamous cell carcinoma (HNSCC) is the sixth most common malignancy worldwide and affects 600 000 new patients each year . In this work, we first collected tumor tissues from three patients bearing different regions of HNSCC to develop PDX cell/mouse models ( Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, by using PDX models, we tested the feasibility of the cell membrane‐coated nanoplatform in a preclinical cancer treatment scenario. Head and neck squamous cell carcinoma (HNSCC) is the sixth most common malignancy worldwide and affects 600 000 new patients each year . In this work, we first collected tumor tissues from three patients bearing different regions of HNSCC to develop PDX cell/mouse models ( Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Tid1 gene knockdown enhances cancer cell malignancy such as cell migration and invasion in vitro, and tumorigenicity in vivo [15]. Additionally, Tid1 abrogates the Galectin-7/TCF3/MMP9 axis to repress the cancer metastasis [16]. We also report the participation of Tid1 in early embryogenesis [20], T cells development [21], muscular development and mitochondrial biogenesis [22] in normal development.…”
Section: Introductionmentioning
confidence: 63%
“…Tid1 has been identified as a tumor suppressor [15][16][17][18][19]. Previously, we have demonstrated that cell proliferation is inhibited in Tid1 overexpressed head and neck squamous cell carcinoma (HNSCC) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Tid1, acting as a tumor suppressor, interacts with EGFR/HSP70/HSP90 by DnaJ domain and causes EGFR degradation in non-small cell lung cancer (NSCLC) [ 18 ] and in head and neck squamous cell carcinoma (HNSCC). Overexpression of Tid1 in HNSCC cell lines enables the inhibition of in vitro malignancy and in vivo xenotransplantation tumorigenicity and metastasis [ 19 ]. Additionally, we reported that the HNSCC patients with higher expression of Tid1 have better overall survival [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Tid1 in HNSCC cell lines enables the inhibition of in vitro malignancy and in vivo xenotransplantation tumorigenicity and metastasis [ 19 ]. Additionally, we reported that the HNSCC patients with higher expression of Tid1 have better overall survival [ 19 , 20 ]. Most recently, we also discovered that Tid1 can function as a tumor suppressor in gastric cancer progression [ 21 ].…”
Section: Introductionmentioning
confidence: 99%